Loan deliquency by businessmen – a study with special reference to public sector banks in coimbatore district - R, Velmurugan; S, Benjamin Christopher (Journal of Management and Science, 2013)
The quality and performance of advances have a direct bearing on the profitability and viability of banks. Despite an efficient credit appraisal and disbursement mechanism, problems can still arise due to various factors. In this regard, a study has been undertaken to examine the behavior of borrowers in repaying the loan taken from public sector banks. The objectives of the study are to examine the socioeconomic background of sample businessmen, to find out factors determining default by businessmen and to suggest methods to improve recovery of NPA. The data required for the study have been collected through an interview schedule. One hundred and twelve borrowers of public sector banks in Coimbatore district are included in the sample. The data collected have been analysed by making use of simple percentage. In order to ascertain the relationship between the various factors and level of NPA Chi-square tests have been followed. The present study carried out in this direction has highlighted the causes for default on the part of the borrowers. Studies on NPA will throw morelight on the burningissue.